An Updated Review on Properties and Indications of Calcium Silicate-Based Cements in Endodontic Therapy - Fateme Eskandari; Alireza Razavian; Rozhina Hamidi; Khadije Yousefi; Susan Borzou (International Journal of Dentistry)
Regarding the common use of calcium silicate cements (CSCs) in root canal therapy, their position in the context of past and present dentistry agents can provide a better understanding of these materials for their further improvement. In this context, the present review article addresses a wide range of recent investigations in the field of CSC-based products and describes details of their composition, properties, and clinical applications. The need for maintaining or reconstructing tooth structure has increased in contemporary endodontic treatment approaches. This research thus discusses the attempts to create comprehensive data collection regarding calcium ion release, bond strength, alkalinizing activity and bioactivity, and the ability to stimulate the formation of hydroxyapatite as a bioactive feature of CSCs. Sealing ability is also highlighted as a predictor for apical and coronal microleakage which is crucial for the long-term prognosis of root canal treatment integrity. Other claimed properties such as radiopacity, porosity, and solubility are also investigated. Extended setting time is also mentioned as a well-known drawback of CSCs. Then, clinical applications of CSCs in vital pulp therapies such as pulpotomy, apexification, and direct pulp capping are reviewed. CSCs have shown their benefits in root perforation treatments and also as root canal sealers and end-filling materials. Nowadays, conventional endodontic treatments are replaced by regenerative therapies to save more dynamic and reliable hard and soft tissues. CSCs play a crucial role in this modern approach. This review article is an attempt to summarize the latest studies on the clinical properties of CSCs to shed light on the future generation of treatments.